ASSISTING THE STUDENTS MASTERING LITERARY TEXT COMPREHENSION THROUGH SCHEMATA - Joni Susanto; Chindy Hanggara Rosa Indah (Facta Universitatis. Series, Teaching, Learning and Teacher Education, 2021)
Reading comprehension presents one of the ways of getting some information and the information that readers read differs one from another. Understanding different information is influenced by reader’s previous knowledge: the more previous knowledge readers have, the better they understand the text read. Considering that there are different texts genres, the texts within one genres are designed in a manner that each of them has their own writing style. As an assistance to memorize the facts related on the reading comprehension and to understand what is read, and when it is about all texts genres, the schemata technique is used. Some researchers states that in the readers’ memory there is predictable structure of knowledge which can be taken as a base that the readers, using these structures in reading, understand all texts genres easily. For improving students’ abilities to master the literature texts, especially the prose and poetic texts, the schemata technique is applied in this research. In the preliminary study, it is determined that the student’s achievements in mastering the prose texts were below the set criteria of the success, and that students were less motivated to learn, too. Students achieved an average of 70.20 points, while the criteria of the success set by the STIBA Academy were 75.00. After applying the schemata technique, students achieved an average of 85.85 points in the prose course and were more motivated to learn. In the preliminary study, in the poetry course, students achieved an average of 66.05 points, and the motivation to learn was low. After applying the schemata technique, students achieved an average of 84.15 points, and the motivation to learn increased. Based on the obtained results, it can be concluded that the application of the schemata technique affects the improvement of students' abilities to understand literary texts, especially prose and poetry, as well as their motivation to study these contents.